Women and their social roles in the folk tale for children (Journal of the College of Basic Education, 2023)
In the folk tales of children, women have received remarkable care, as their roles varied between the supportive wife, the tender mother, the successful leader, and others. Many folk tales that were not employed in children's literature, in which women played the role of absolute heroism and defeated men, as in the story of (Sitt al-Hassan), the story of (the bride and the pharaoh), the story of (the beggar's daughter), the story of (the cat and the daughter of thorns) and the story of (the smart girl), and this is what makes us repeat Considering that the environment had an impact on the storytelling directed at the child, it did not give much space to women for many reasons, including: the nature of the society, the dominance of the male society, most of the writers were males.